Kepatuhan Wajib Pajak: Faktor-Faktor Yang Mempengaruhinya(Studi Pada Wajib Pajak Pp 46 Tahun 2013 Yang Terdaftar Di Kpp Pratama Surakarta Dan Boyolali) - Nur Khasanah, Lia, Drs. Muhammad Abdul Aris, M.Si (2017)
ABSTRACT The purpose of this study to analyze the effect of the benefits of TIN, taxpayer understanding, quality of services, tax sanctions, socialization of taxation, and tax rate on tax compliance. This study is quantitative research. This study population taxpayer listed on tax office (KPP) Pratama Surakarta and Boyolali. Primary data collection method used is a survey method using questionnaires media. Sampling was done by convenience sampling method. The number of questionnaires that can be analyzed is 100 questionnaires. Data analysis techniques used in this research is logistic regression analysis.The results of this research showed that Benefits of TIN, taxpayer understanding, sanctions, socialization of taxation, and tax rate significant effect on tax Compliance. Quality of services had no significant effect on tax compliance. Keywords: Tax Compliance